The Utilization of Multimodal Media with the Project Based Learning Model on the Learning Achievement - Dita Yunilasari; Sriyanto Sriyanto (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
This research is motivated by the low learning achievement of Natural and Social Sciences (IPAS) of grade IV students at SD Negeri 1 Bodaskarangjati which is not optimal due to the use of conventional learning methods that are not in accordance with the diversity of students’ learning styles. This study aims to analyze the effectiveness of the use of multimodal media in the Project-Based Learning (PjBL) model on improving student learning achievement. The method used was a pre-experiment with a One-Group Pretest-Posttest design on 22 students. Data was collected through multiple-choice tests that had been tested for validity and reliability, then analyzed using N-Gain tests, t-tests, and effect size tests. The results showed a significant increase in the average score from 68.53 to 83.22 with an N-Gain value of 0.47 (medium category) and an effect size of 1.39 (very large). In addition, there is a decrease in the ability gap between students. In conclusion, the application of multimodal media in the PjBL model is effective in increasing social studies learning achievement and being able to accommodate the diversity of students’ learning styles in a more inclusive and adaptive manner.